BLT2 expression improves skin integrity and protects from alterations caused by hyperglycemia in type 2 diabetes. Issue 1 (1st January 2017) - Leguina-Ruzzi, Alberto; Valderas, Juan P.
ABSTRACT: Type 2 diabetes (T2D) can go undiagnosed for years, leading to a stage where chronic high blood sugar produces complications such as delayed wound healing. Reports have shown that BLT2 activation improves keratinocyte migration and wound healing, as well as protecting the epidermal barrier through the promotion of actin polymerization. The goal of this study was to elucidate the role of BLT2 expression in skin epithelial integrity in T2D. For this purpose, we used both wild type (WT) and BLT2 knockout mice in a model, in which a T2D-like phenotype was induced by keeping the animals on a high fat (HF) diet over 5 weeks. In a parallel in vitro approach, we cultured BLT2-transfected HaCaT cells at both low and high glucose concentrations for 48 h. Structure, transepithelial resistance (TEER), IL-1ß, IL-8 or CXCL2, MMP9, Filaggrin, Loricrin and Keratin 10 (K10) were evaluated ex vivo and in vitro . Additionally, wound healing (WH) was studied in vitro . The skin from T2D and BLT2 knockout mice showed a reduction in TEER and the expression of IL-1ß, and in increase in CXCL2, MMP9, Filaggrin, Loricrin and K10 expression. The structure suggested an atrophic epidermis; however, the skin was dramatically affected in the BLT2 knockout mice kept on a HF diet. HaCaT-BLT2 cells presented as an organized monolayer and showed higher TEER and wound healing compared with vector only-transfected HaCaT-Mock cells. Likewise, alterations in the expression of skin inflammatory, matrix degradation and differentiation markers under low and high glucose conditions were less severe than in HaCaT-Mock cells. Our results suggest that BLT2 improves epithelial integrity and function by regulating differentiation markers, cytokines and MMP9. Furthermore, BLT2 attenuates the damaging effects of high glucose levels, thereby accelerating wound healing.